El lenguaje periodístico en la red: del texto al hipertexto y del multimedia al hipermedia. - Edo, Concha (Estudios sobre el Mensaje Periodístico, 2001)
THE JOURNALISTIC LANGUAGE IN THE NET: OF THE TEXT TO THE HYPERTEXT AND OF THE MULTIMEDIA TO THE HYPERMEDIA The technological possibilities with which we have begun the 21st century have produced changes and new ways of telling the current news and affairs. Precisely in this moment is when it is of most importance to define the dimensions of the language 79 Concha Edo Bolós El lenguaje periodístico en la red: del texto al hipertexto y del multimedia al hipermedia fit for the means on line in order to counter the invasion of information that is not prepared by press professionals and yet fill the front pages and web pages in the screen of your computers, and more and more in televisions and mobile telephones. Digital journalism involves the simultaneous use of all the utilities tha t we already know text, sound, pictures, videotapes and fixed or interactive graphics in order to produce a plural language, unifier and multimedia that we will designate from now on multiple and that it is going to be absolutely necessary for a high percentage of journalists all over the world.
Keywords: Internet; Journalistic Language; Written Journalism; Digital Journalism; Electronic Journalism; Hypertext; Hypermedia; Multimedia Language